Xorazm Xalq Sovet Respublikasi davrida agrar sohadagi o‘zgarishlar - Matniyozov Sarvarbek San’atbek o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the reforms and changes implemented by the government of the Khorezm People's Soviet Republic in the agricultural sector, the main sector of the country's economy, under the new regime.